A MACROECONOMIC THEORY OF THE OPEN ECONOMY - Abrorjon Habibullayev Ahmadali ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
If the government of a country wants to reduce trade deficits, what should it do? Should it try to limit imports, perhaps by imposing a quota on the import of cars from Japan or Germany? Or should it try to influence the country’s trade deficit in some other way? The goal of the model in this article is to highlight the forces that determine the economy’s trade balance and exchange rate. In one sense, the model is simple: it applies the tools of supply and demand to an open economy. Yet the model is also more complicated than others we have seen because it involves looking simultaneously at two related markets – the market for loanable funds and the market for foreign currency exchange. After we develop this model of the open economy, we use it to examine how various events and policies affect the economy’s trade balance and exchange rate. We shall then be able to determine the government policies that are most likely to reverse trade deficits.